IMPLEMENTASI METODE BERCERITA TERHADAP KEMAMPUAN BAHASA ANAK USIA 4-5 TAHUN DI PAUD SAHABAT KECAMATAN RAWAMERTA - Karnemi, Dedeh; Fauziah, Debibik Nabilatul; Syafrida, Rina (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Learning activities with the stortelling methood is a learning process that teachers try to develop children’s language skills. Storytelling can foste courage in children by continuing to provide stimulation from direct experience that involves children in learning activities, so it is necessary to prepare storytelling themes so that learning is more creative. The benefits of storytelling are that it helps children’s ability tio listen, children’s imagination power is trained, adds a sense of joy, children will be active and dare to appear in learning. Storytelling is one of the ways children communicate with their peers. The problem in this study is that the child has not paid attention to the words of others, has not been able to understand the contents of the reading that is told, the child has not retold the story that has been heard. This study aims to describe the implementation of language skills through the storytelling method for early childhood friends. Qualitative descriptive is the method used in this research. Data collection techniques using observations, interviews, documentation. The results of data analysis show the implemetation. The results of data analysis show the implementations of the storytelling method in improving children’s language, namely by making lesson plans that can make teaching, directing and educating and stimulating, motivating, by setting a good example to children so that they have languange skill and can increase children’s self-confidence